THE PHENOMENON OF KOREAN POP FANATICISM FROM THE PERSPECTIVE OF THE QUR’AN: A THEMATIC TAFSIR STUDY - Pajriatul Camelia; Muhammad Ilham (Journal of Islamic and Interdisciplinary Research, 2025)
This article aims to provide an understanding of the context of K-Pop fanaticism and its interpretation in the Qur’an. K-Pop is a music industry originating from South Korea that is highly popular and has a large fan base. K-Pop fans consistently show support and loyalty, and often excessively glorify their idols and communities by displaying extreme and obsessive behavior. For this reason, K-Pop fans are frequently labeled as fanatical by society. Therefore, this article discusses the context of K-Pop fanatical behavior from the perspective of the Qur’an, focusing on a thematic analysis of several Qur’anic verses related to fanaticism, using data analysis based on a Systematic Literature Review. The results of this study indicate that fanatical behavior toward K-Pop is prohibited and contradicts the teachings and cultural values of Islam, whereas merely expressing admiration is permissible. Thus, fans are expected to reduce excessive indulgence in foreign cultures and to exercise self-restraint so as not to follow cultural practices that are prohibited by religion, which could otherwise lead to the erosion of local culture and cause individuals to deviate onto an improper path.